Revelation, truth, canon, and interpretation : studies in Justin Martyr's Dialogue with Trypho - Allert, Craig D. (Vigiliae Christianae, Supplements, 2002)
This volume treats the concepts of revelation, truth, canon, and interpretation as four pillars of early Christian theology. Using Justin Martyr as a case-study, his \'Dialogue with Trypho\' is examined with a view toward discerning how a second century Christian father understands and develops these concepts. Justin's intellectual background is discussed within the nuanced context of Middle Platonism. Particular attention is paid to his use of biblical sources which is grounded in the foundational chapter on revelation in Justin. Justin is placed within the wider context of theological developments in pre-Nicene Christianity, and includes a warning against judging Justin by anachronistic post-Nicene developments.